Equitable Use of Subsidized Child Care in Georgia - Thomas Goldring; David C. Ribar (Institute of Labor Economics (IZA), 2024)
High-quality childcare services are vital to children's development and family wellbeing but are not equitably accessed by all children. Programs supported by the Child Care Development Fund (CCDF) have the potential to reduce these inequities. Economically eligible Black children use CCDF-supported services at higher rates than other children, but less is known about disparities in the characteristics of those services. This study uses weekly subsidy records from Georgia's Childcare and Parent Services (CAPS) program to examine racial, ethnic, and geographic differences in the types, modes, quality, proximity, and stability of care and in subsidy payments, co-payments, and subsidy use. The study distinguishes between unconditional differences that it observes in children's experiences and conditional disparities that it estimates after accounting for children's needs and other characteristics. It interprets the conditional disparities as evidence of inequity. The analysis uncovers many unconditional racial and ethnic differences in subsidized care outcomes and several geographic differences. However, the study finds fewer (and mostly smaller) conditional differences, including very few conditional differences between non-Hispanic Black and White children. The results suggest that there is substantial equity in participating children's use of CAPS services.
Keywords: J13; I38; 330; equity; childcare arrangements; subsidized child care; race and ethnicity; geography; administrative data; Georgia